Influencer’s Trustworthiness and Attitude to Increase Purchase Intention in Generation Z Based on Theory of Planned Behavior - Sabina, Azkiya Salis; Marsasi, Endy Gunanto (LPPM Universitas Trunojoyo Madura, 2024)
The aim of this study is to examine the correlation between the trustworthiness of influencers and the attitude of Generation Z in influencing their intention to make purchases, utilizing the theory of planned behavior. This study utilizes a quantitative approach and applies a purposive sampling procedure to collect a total of 218 samples. The analysis is performed using Structural Equation Modeling (SEM) and aided by AMOS 24 Graphics software. This study discovered a significant positive correlation between online customer reviews and attitude. Attitude has a significant positive correlation with brand loyalty, purchase intention, and electronic word of mouth. Brand loyalty also has a significant positive correlation with purchase intention. There are new findings, namely a significant positive correlation between influencer's trustworthiness and attitude, and electronic word of mouth has a significant negative correlation to purchase intention. This study has implications for companies regarding product quality and consistency of product ratings that cause eWOM to have a negative relationship with purchase intentions. This research has an update on the variable, namely the influencer's trustworthiness, to measure influencer trust in consumers.